2016
DOI: 10.1002/clen.201500366
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Anti‐Biofouling, and Antioxidant Prospects of Metal‐Based Nanomaterials

Abstract: Three metallic nanomaterials, i.e., iron, copper, and bimetallic iron-copper were easily synthesized using a wet-chemical method and were properly characterized. The materials were tested against two bacterial strains, Staphylococcus aureus and Escherichia coli in order to evaluate their antibacterial activity, as well as their biofilm formation inhibition properties. The total inhibition of bacterial growth, at low mg/mL concentrations, implies the satisfactory antibacterial activity of the nanomaterials agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Analysis of variance showed that FCFNCs at 750 µg mL −1 caused significant inhibition ( P ˂ 0.05) of biofilm growth in S. aureus (90.6 ± 1.3%) and P. aeruginosa (76.11 ± 1.17%). In comparison, Chatzimitakos and coworkers 46 found that 100 mg/mL of CuFe nanohybrid corrupted the biofilm formation of E. coli and S. aureus by 12 and 49%, respectively, proofing the efficiency of our FCFNCs in minuscule amounts.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Analysis of variance showed that FCFNCs at 750 µg mL −1 caused significant inhibition ( P ˂ 0.05) of biofilm growth in S. aureus (90.6 ± 1.3%) and P. aeruginosa (76.11 ± 1.17%). In comparison, Chatzimitakos and coworkers 46 found that 100 mg/mL of CuFe nanohybrid corrupted the biofilm formation of E. coli and S. aureus by 12 and 49%, respectively, proofing the efficiency of our FCFNCs in minuscule amounts.…”
Section: Resultsmentioning
confidence: 55%
“…Remarkably, various microbial biomolecules could participate substantially in the reduction phase and chelating activity to transform metal ions into their NPs analogues, including NADH-dependent enzymes, such as cytochrome reductase, hydrogenases, nitrate reductase, dehydrogenases 4 , superoxide dismutase and catalase 46 . Actually, in the biological redox reaction, the enzymes shuttle electrons to the metal ions that were reduced to the NPs through sequential variation in their oxidation states.…”
Section: Resultsmentioning
confidence: 99%
“…DPPH free radical scavenging, inhibition of lipid peroxidation, metal chelating activity, reducing power and prevention of oxidative damage to proteins were examined following previously reported methods [42,51].…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…Silver nanoparticles have been reported to be applied to adsorb Cr(II) and Pb(II) as suspended free nanoparticles in the system [12]. Copper nanoparticles were used as antibiofouling, antioxidant and antibacterial agents for wastewater treatment [36]. Those nanoparticles showed efficiency in inactivation of pathogens, inhibition of lipid oxidation and biofilm formation and scavenging free radicals.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%